(untitled) (Indian Journal of Public Health Research & Development, 2020)
Laboratory safety is one aspect that must be considered. A variety of chemical materials contained in the laboratory, causing the potential for workplace accidents in high-risk laboratories. Accidents at work that occur in laboratories greatly affect the business and the community environment. The purpose of this study is to discover how much benefit in economic value of implementation of occupational safety and health in the laboratory. This research is explained about the method for cost benefit analysis of occupational health and safety in laboratory. This research was conducted at the campus laboratory. This study focuses on procuring implementation of occupational health and safety for the types of work that use chemicals in laboratory, based on government regulation in Indonesia. With effective application of occupational health and safety, the benefits that campus university perceive are reduced costs of replacing sick, sick leave, so operational costs will be lower, other disruptions in the production process will also be reduced and produce profits for entrepreneurs. Implementation of OSH of this laboratory requires adequate planning. Therefore the implementation must be coordinated by a Health and Safety team that works closely with various other professionals in the laboratory, with special emphasis on finance, management control and the human resources department.